Global Variation in Escherichia coli mcr-1 Genes and Plasmids from Animal and Human Genomes Following Colistin Usage Restrictions in Livestock - Biel Garcias; Mayra Alejandra Flores; Mercedes Fernández; William Monteith; Ben Pascoe; Samuel K. Sheppard; Marga Martín; Martí Cortey; Laila Darwich (MDPI AG, 2024)
Antimicrobial resistance (AMR) is a significant global health threat, with multidrug-resistant (MDR) bacterial clones becoming a major concern. Polymyxins, especially colistin, have reemerged as last-resort treatments for MDR Gram-negative infections. However, colistin use in livestock has spread mobile colistin resistance (mcr) genes, notably mcr-1, impacting human health. In consequence, its livestock use was banned in 2017, originating a natural experiment to study bacterial adaptation. The aim of this work was to analyse the changes in the mcr-1 genetic background after colistin restriction across the world. This study analyses 3163 Escherichia coli genomes with the mcr-1 gene from human and livestock hosts, mainly from Asia (n = 2621) and Europe (n = 359). Genetic characterisation identifies IncI2 (40.4%), IncX4 (26.7%), and multidrug-resistant IncHI2 (18.8%) as the most common plasmids carrying mcr-1. There were differences in plasmids between continents, with IncX4 (56.6%) being the most common in Europe, while IncI2 (44.8%) was predominant in Asia. Promoter variants related to reduced fitness costs and ISApl1 showed a distinct pattern of association that appears to be associated with adaptation to colistin restriction, which differed between continents. Thus, after the colistin ban, Europe saw a shift to specialised mcr-1 plasmids as IncX4, while ISApl1 decreased in Asia due to changes in the prevalence of the distinct promoter variants. These analyses illustrate the evolution of mcr-1 adaptation following colistin use restrictions and the need for region-specific strategies against AMR following colistin restrictions.